The Culture Aspect of Javanese and Chinese Acculturation In Lasem - Basiroen, Vera Jenny; Manuaba, Ida Bagus Kerthyayana (Humaniora: Journal of Indonesia Culture and Society, 2022)
The research aimed to document the history and culture of Lasem, thereby increasing the knowledge base of cultural history in Indonesia. The interaction between Javanese and Chinese in Lasem experienced three phases: the Zheng He period, the Yellow War period, and the 20th century. Relations between Javanese and Chinese had been peaceful and harmonious until now. In the middle of the 18th century, there were incidents of violence against ethnic Chinese carried out by the company. This event led to the strengthening of relations between Java and China. The collaboration between the two became a momentous event that the Lasem residents could not forget. Harmonious life in Lasem was not only seen in batik. Still, it was also seen in the daily life of the Lasem people, such as togetherness in celebrations, religious rituals, or family rituals. There were three research questions: What was the process of acculturation in Lasem? What cultural elements underwent acculturation, and what were the results of acculturation? The research applied a qualitative narrative method by collecting data from the literature, interviewing cultural observers, observing, and analyzing. The research discussed the results of acculturation in Lasem in several forms of culture, namely in language, architecture, batik, and rituals. The results of the research indicate that harmonious inter-ethnic life in Lasem can embrace all Indonesian citizens in revive the spirit harmoniously.